EFFECT OF TEMPERATURE ON THE STRESS-STRAIGHTENING STATE OF A TWO-SUPPORT LOCKING THREADED CONNECTION OF WEIGHTED DRILL PIPES - Artym, V. I.; Novoselskyi, B. A. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY. Number, 2025)
The article presents the results of a study of the effect of temperature on the stress-strain state of a screwed two-support lock threaded connection of weighted drill pipes. It has been established that temperature significantly affects the geometric parameters, fit accuracy, and strength of threaded connections, since thermal expansion changes the tightening forces that determine the tightness and durability of the connection. For the study, a three-dimensional model of an NC50 double-support connection was constructed, which takes into account the effect of the temperature gradient (from 20 °C inside to 100 °C outside) and the tightening torque. Modeling was performed in SolidWorks FlowSimulation with subsequent export of thermal loads to Simulation to determine the stress-strain state. It was shown that the temperature distribution in the connection is uneven. A comparative analysis of the distribution of equivalent stresses in the recesses of the nipple coils, taking into account the temperature gradient and the tightening torque, showed both their increase and decrease relative to the case of only the tightening torque acting on a two-support ZRZ. This confirms the significant influence of the temperature field on the stress-strain state of the connection. The greatest reduction in stresses is observed in the first and last threads of the nipple, which can contribute to an increase in the durability and fatigue strength of the threaded connection, but at the same time there is a possibility of deterioration in its tightness. The results obtained are consistent with known experimental data and confirm the feasibility of taking thermomechanical factors into account when calculating the strength of drill strings. The modeling method used can be adapted to analyze other types of oil and gas equipment connections, in particular pump and compressor pipes and casing pipes operating in high-temperature conditions, with a view to further improving them to increase reliability, durability, and operational safety.